中國大陸幼兒教師之日常實踐創新知覺研究 A Study on the Innovation Perceptions of Daily Practices of Early Childhood Teachers in Mainland China - 陳南希 Nanxi Chen (National Taiwan Normal University, 2021)
幼兒教師對於創新的認識知識會影響他們的創新實踐。本研究借鑑個體創新的文獻，透過應用質性研究方法，闡明幼兒教師對日常創新的理解。參與者是來自中國大陸的六名幼兒教師。分析資料來自於圍繞幼兒教師對其日常創新與實踐之知覺的半結構訪談，訪談內容包括：一、個人的「創新」概念；二、日常工作中創新實踐的例子；三、創新分享；四、影響創新實踐的因素。本研究採紮根理論取向分析方法對訪談資料進行編碼與歸類。本研究發現，對於創新的認知，受訪的幼兒教師認為其日常創新實踐是多元的，並融入了他們自己對孩子的教育理念。他們還將日常創新理解為有影響力之想法的產生與實施，以及解決問題。此外，幼兒教師在影響其創新實踐的因素方面具有系統的意識，知覺到多種內部因素（即人格和特質、內在動機、個人經驗及專業能力）與外部因素（即是否在任務層面、人際關係層面、組織領導層面及本地生態層面上獲得支持）。本研究從過程知識生產的角度對相關發現進行討 論，就幼兒教師對其日常實踐創新之認識做更深入的理解，並期為幼兒教師專業發展相關議題提供啟示。 Early childhood (EC) teachers' epistemic knowledge about innovation can influence their innovative practice. Drawing on literature from the field of individual innovation, this study was conducted to clarify EC teachers' understanding of their daily innovation by applying a qualitative approach. The participants included six EC teachers from Mainland China. To understand the teachers' perception of innovation in their daily practice, the following elements were defined: (1) the teachers' personal conception of innovation, (2) examples of innovative practice in their daily work, (3) innovation sharing, and (4) factors influencing innovative practice. Regarding personal conceptions of innovation, this study found that the interviewed EC teachers perceive their daily innovation practice to be multidimensional and to involve their own educational philosophy.The teachers also understand daily innovation to mean the generation and implementation of influential ideas as well as problem-solving. Regarding factors that influence their innovation practice, this study determined that the teachers possessed a systematic sense with awareness of both internal factors (i.e., personalities and traits, intrinsic motivation, personal experience, and professional capacity) and external ones (i.e., whether there is support available at the task level, interpersonal level, organizational leadership level, or local ecological level). This study offers a discussion about perspectives on the process of knowledge production to better understand EC teachers' ideas about innovation in their daily practice.